2008
DOI: 10.1152/ajprenal.00547.2007
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1/CCR2 system is involved in high glucose-induced fibronectin and type IV collagen expression in cultured mesangial cells

Abstract: ) is a potent chemokine that plays an important role in the recruitment of macrophages. Although previous studies have demonstrated the importance of MCP-1 in the pathogenesis of diabetic nephropathy (DN) in terms of inflammation, the role of MCP-1 and its receptor (C-C chemokine receptor 2; CCR2) in extracellular matrix (ECM) accumulation under diabetic conditions has been largely unexplored. This study was undertaken to investigate the functional role of the MCP-1/CCR2 system in high glucoseinduced ECM (fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 38 publications
3
46
0
1
Order By: Relevance
“…Collagen metabolism disorders play an important role in the pathogenesis of DN. 19 TGF-b1 is considered an important etiologic factor in interstitial fibrosis by increasing the production of ECM. In addition, its upregulation is a common characteristic of renal tubulointerstitial fibrosis in DN.…”
Section: Effects Of Nctd On Can/nfatc Signaling Pathway In Hk-2 Cellsmentioning
confidence: 99%
“…Collagen metabolism disorders play an important role in the pathogenesis of DN. 19 TGF-b1 is considered an important etiologic factor in interstitial fibrosis by increasing the production of ECM. In addition, its upregulation is a common characteristic of renal tubulointerstitial fibrosis in DN.…”
Section: Effects Of Nctd On Can/nfatc Signaling Pathway In Hk-2 Cellsmentioning
confidence: 99%
“…MCP-1 directly increased fibronectin production in cultured mesangial cells. 17,19 Recently, we also found that MCP-1 directly induced podocyte apoptosis. 18 In addition, MCP-1 itself induced intercellular adhesion molecule-1 and fibronectin expression in cultured mesangial cells.…”
Section: Discussionmentioning
confidence: 93%
“…17 The kits for human MCP-1 were species specific and sensitive up to 5.0 pg/ml. The minimum sensitivity for human TGF-b1 of the kit used in this study was 4.6 pg/ml.…”
Section: Elisamentioning
confidence: 99%
See 2 more Smart Citations